Stakeholder Collaboration in Handling Stunting and Malnutrition Cases in Mekarjaya Subdistrict, Pandeglang District - Aas Aseni; Jumanah (International Publisher (YAPENBI), 2025)
Stunting and malnutrition remain significant public health issues in Pandeglang District, including in the Mekarjaya Subdistrict. Effective intervention requires cross-sectoral collaboration among stakeholders such as local government, health workers, communities, and other actors. This study aims to analyze the forms of stakeholder collaboration in addressing stunting and malnutrition cases, identify existing challenges, and formulate strategies to strengthen local-level cooperation. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews, observations, and documentation involving key informants such as the subdistrict head, head of the public health center, village heads, and posyandu (integrated health post) cadres. The findings show that the collaboration among stakeholders remains sectoral and lacks systematic integration. Weak coordination, the absence of local regulations, and underutilized local potential and wisdom are the main obstacles. However, there is potential for improvement through the establishment of intersectoral forums, capacity building for community health workers, and localized program adaptation. The study recommends developing collaborative local regulations and sustainable coordination mechanisms to accelerate the reduction of stunting and malnutrition in a holistic manner.